Transformações urbanas na cidade de São Carlos: condomínios horizontais fechados e novas formas de sociabilidade - Ferreira, Francisco Barnabé (Universidade Federal de São Carlos, 2007)
The present work aims to analyze the recent growing process of the city of São Carlos - SP and its social relations net in terms of urban occupation, which has been under substantial changes since the end of the 20th century, especially after the implementation of private horizontal residential areas in the suburbs of the city. These transformations are intrinsically connected to the changes in use and meaning of the central areas and its implications for the municeps. As it is possible to observe along the work, the concept of mixed land-use has different meanings. For some authors downtown, which has started to be occupied by commerce and service industry, has also been struck by the incidence of social conflicts found in mid-size cities, due to problems stemming from unwanted interactions, traffic, heterogeneity, violence, fear and unpredictability of the streets, thus changing both the public and private spaces, especially those earlier linked to the activities of the wealthiest social classes. For other authors, on the other hand, the mixed land-use in central areas presents positive features, such as the increase in cooperation and sociability, thanks to the creation of a net of relations among the inhabitants, which tends to boost the trust of the population. In order to make an analysis of these transformations possible, we have used interviews carried out with dwellers, workers and home help of two private residential areas in the city of São Carlos: Parque Faber I and Parque Fehr , chosen according to their particularities, which will be exposed in this study. Besides, we have included an ethnography of Parque Faber I , as well as pictures taken in these places, because they bring to light aspects not always explicit in the interviews. It is important to highlight that we consider the interpretation of marketing material on this new dwelling concept relevant so as to analyze the sales appeal of entrepreneurs and construction firms involved in the projects of the private residential areas. The consequences of such transformations in the urban fabric affect directly the life of its inhabitants, who tend to occupy the urban land in a more segregated way, in an attempt to get rid of the problems arisen by the swelling of downtown. This attitude also creates new conflicts and inequalities around unique sociabilities, such as those found in private horizontal residential areas, object of this research.
Keywords: Francisco Barnabé Ferreira; Condomínios fechados; Sociabilidade; Urbanização; Violência; CIENCIAS HUMANAS